Maintaining Value, Welcoming Innovation: Challenges and Reconstruction of Sharia Economic Law in the Development of Sharia Fintech in Indonesia - Genta Buana Arfianto Putra; Ibrahim Nanda Pratama; Erenz Erico; Rindingpadang; Prima Raharja Mulyana; Baidhowi (Takaza Innovatix Labs Ltd., 2025)
The development of digital technology has transformed the global financial system, including the sharia economic ecosystem in Indonesia. The emergence of sharia financial technology (fintech) presents both an opportunity and a challenge for sharia economic law to remain relevant without abandoning its fundamental values. On the one hand, digital innovation opens broader and more inclusive access to financing; on the other hand, issues arise regarding sharia compliance, legal certainty, and regulatory harmonization between fatwas and laws and regulations. This article aims to analyze how sharia economic law adapts to the development of sharia fintech and assess the conformity of regulations issued by the Financial Services Authority (OJK) with sharia principles as stipulated by the National Sharia Council of the Indonesian Ulema Council (MUI). This research uses a normative juridical method with a statutory and conceptual approach. The results of the study indicate that normatively, sharia fintech regulations in Indonesia have accommodated basic principles such as the prohibition of usury (riba), gharar (gharar), and maysir (gambling). However, challenges remain in the interpretation of digital contracts, technology-based supervision, and responding to rapidly evolving innovations. Therefore, a reconstruction of Islamic economic law is needed that is not only oriented towards formal compliance but also adheres to the maqasid of sharia, the spirit of the Islamic economic system.